2019
DOI: 10.1186/s13690-019-0365-x
|View full text |Cite
|
Sign up to set email alerts
|

Low prevalence of syphilis infection among key populations in Togo in 2017: a national cross-sectional survey

Abstract: Background: The World Health Organisation (WHO) recommends the screening of syphilis among populations highly exposed to HIV. However, data on the prevalence of syphilis in these populations are scarce in Togo. This study aimed at estimating the prevalence of syphilis among males who have sex with males (MSM), female sex workers (FSW) and drug users (DU) in Togo. Methods: A cross-sectional bio-behavioral study was conducted in August and September 2017 using a respondent-driven sampling (RDS) method in eight m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…21 However, a study conducted in Togo showed there was no relation between HIV status and syphilis infection. 22 In our study, the odds of Syphilis-HIV co-infection was 1.62-times higher among FSWs who had experienced condom breakage in the last 30 days compared to FSWs who had not experienced condom breakage in the last 30 days. This finding was in line with the findings from a study conducted in Dessei town which showed condom breakage was associated with an increasing prevalence of STI.…”
Section: Discussionmentioning
confidence: 41%
“…21 However, a study conducted in Togo showed there was no relation between HIV status and syphilis infection. 22 In our study, the odds of Syphilis-HIV co-infection was 1.62-times higher among FSWs who had experienced condom breakage in the last 30 days compared to FSWs who had not experienced condom breakage in the last 30 days. This finding was in line with the findings from a study conducted in Dessei town which showed condom breakage was associated with an increasing prevalence of STI.…”
Section: Discussionmentioning
confidence: 41%
“…People who are sexual minorities and marginalized and disproportionately affected by HIV— particularly, homosexual men, bisexual men, and male-to-female transgender people, are known together as ‘‘men who have sex with men (MSM)’’ [ 1 ]. The MSM is the most vulnerable group of people who are being at a high level of risk of HIV and sexually transmitted infections (STIs) in Asia due to unprotected anal sex, heterosexuality, multiple sex partners, etc [ [2] , [3] , [4] , [5] ]. Globally in 2018, the chance of being infected with HIV in gay men was 22 times higher than in all-adult men [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…People who are sexual minorities and marginalized and disproportionately affected by HIV-particularly, homosexual men, bisexual men, and male-to-female transgender people, are known together as ''men who have sex with men (MSM)'' [1]. The MSM is the most vulnerable group of people who are being at a high level of risk of HIV and sexually transmitted infections (STIs) in Asia due to unprotected anal sex, heterosexuality, multiple sex partners, etc [2][3][4][5]. Globally in 2018, the chance of being infected with HIV in gay men was 22 times higher than the all-adult men [6].…”
Section: Introductionmentioning
confidence: 99%